1997
DOI: 10.1111/j.1365-2044.1997.121-az0115.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationship and effective time to satisfactory intubation conditions after rocuronium in children

Abstract: SummaryWe assessed the neuromuscular blocking effects of, and intubation conditions following, rocuronium in 81 children aged 2-12 years. The study was conducted in three parts. Parts 1 and 2 were undertaken during anaesthesia with thiopentone, alfentanil and nitrous oxide. Neuromuscular blockade was evaluated by recording the force of contraction of the adductor pollicis in response to train-of-four stimulation at 2 Hz repeated every 10 s. In Part 1 the potency of rocuronium was determined in 15 children usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…A outra explicação para as condições ruins pode ter sido o tempo insuficiente de instalação do bloqueador neuromuscular. Hopkins e col. 25 indicaram que, para a dose de 0,6 mg.kg -1 de rocurônio, o tempo ideal para a obtenção de melhores condições está em torno de 70 segundos. Diferenças no comportamento do relaxamento entre crianças e adultos têm sido identificadas 26 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A outra explicação para as condições ruins pode ter sido o tempo insuficiente de instalação do bloqueador neuromuscular. Hopkins e col. 25 indicaram que, para a dose de 0,6 mg.kg -1 de rocurônio, o tempo ideal para a obtenção de melhores condições está em torno de 70 segundos. Diferenças no comportamento do relaxamento entre crianças e adultos têm sido identificadas 26 .…”
Section: Discussionunclassified
“…A different explanation for poor conditions could have been insufficient time for relaxation. Hopkins et al 25 have indicated that for 0.6 mg.kg -1 rocuronium, optimal time to obtain best conditions is approximately 70 seconds. Differences in relaxation behavior in children and adults have already been identified 26 , among them potency.…”
Section: Discussionmentioning
confidence: 99%
“…All children enrolled had either Mallampati class I or II and no contraindication for rapid sequence induction of anaesthesia. [5][6][7][8] Pre-Anaesthetic Check-up (PAC) and necessary investigations done on the day before surgery to ascertain the medical and physical fitness. Selected patients were divided into Three Groups.…”
Section: Methodsmentioning
confidence: 99%
“…In children anesthetized with thiopental-nitrous oxide, satisfactory intubating conditions were observed in 98 and 100% of cases 90 and 70 s after the administration of 2 Â ED 95 doses of mivacurium or rocuronium, respectively [26,27]. Similarly, in a study of 60 children aged 2-7 years, good/excellent intubating conditions were achieved in all patients at 1 MAC anesthesia with sevoflurane 2 min after injection of rocuronium 0.3 mg/kg (around 1 Â ED 95 ) [28].…”
Section: Balanced Anesthesia With a Nondepolarizing Muscle Relaxantmentioning
confidence: 99%